„Soil Vapour Intrusion“ – A new model for the determination of indoor air concentrations - Putzmann, Thomas; de Biase, Cecilia; Loechel, Sarah; Bittens, Martin; Weiss, Holger (Águas Subterrâneas, 2011)
Emissions of volatile organic compounds (VOCs) from groundwater sources to indoor air (vapour intrusion) represent a relevant risk driving process in urban environments. Simulated vapour intrusion in lab scale experiments and the application of a field module at contaminated sites help to understand the mechanism of diffusive and convective transport of pollutants in the unsaturated soil zone and through concrete as diffusion barrier. With the data sets from lab and field scale experiments of the UFZ, a new prediction tool for the estimation of VOC concentrations in indoor air was developed. The model, Soil Vapour Intrusion (SVI), can be used for forward and backward calculations of VOC concentrations and also integrates the diffusive behaviour through sealing materials.